Cover Image. (4th August 2021) - Liu, Weibo; Fortier, Richard; Molson, John; Lemieux, Jean‐Michel
Abstract : The cover image is based on the Research Article A conceptual model for talik dynamics and icing formation in a river floodplain in the continuous permafrost zone at Salluit, Nunavik (Quebec), Canada by Weibo Liu et al., https://doi.org/10.1002/ppp.2111 .